STUDI PENGURANGAN EMISI KARBON SISTEM KETENAGALISTRIKAN PROVINSI BALI: ANALISIS RUPTL 2021-2030 - Putra Purnomo, Aditya Perdana; Dwi Giriantari, Ida Ayu; Satya Kumara, I Nyoman (Jurnal SPEKTRUM; Vol 10 No 3 (2023): Jurnal SPEKTRUM, 2023)
Indonesia's Nationally Determined Contribution (NDC) targets a 19 to 27% reduction in greenhouse gas (GHG) emissions from the energy sector compared to the business-as-usual scenario. Assuming this target applies uniformly to all provinces in Indonesia, including the power sector, a modeling analysis of Bali's power system is conducted to assess GHG emission reductions. Two scenarios are developed in the Low Emissions Analysis Platform (LEAP) to evaluate the future deployment of Bali's power system. The Business-As-Usual (BaU) scenario serves as the baseline for emission reduction in other scenarios and assumes the development of Bali's power system without emission reduction interventions. The RUPTL scenario assumes the continued development of Bali's power system in line with the electricity development plan document. Results show that the RUPTL scenario achieves a 20.89% reduction in emissions, which fulfills the regional assumption of a 19% NDC target. However, it falls short of achieving the 2030 target of 27% emission reduction.